2006
DOI: 10.1002/pds.1296
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion in pregnancy and the prevalence of congenital malformations

Abstract: Results do not support a hypothesis of a teratogenic effect of first trimester bupropion exposure. The prevalence of malformations associated with bupropion exposure in the first trimester was not increased relative to the comparison groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 27 publications
4
102
0
Order By: Relevance
“…One high risk of bias observational study reported no increase in risk of congenital malformations associated with the use of bupropion during pregnancy compared with other antidepressants as a group in women with depression during pregnancy. 153 Indirect evidence from a larger (N=7005), medium risk of bias study, also reported no statistically significant increase in risk with bupropion compared with other antidepressants reported an adjusted OR of 0.95 (95% CI, 0.62 to 1.45), 40 Depression status of women in either group was not known in this study.…”
Section: Class Compared With Class: Selective Serotonin Reuptake Inhimentioning
confidence: 64%
See 2 more Smart Citations
“…One high risk of bias observational study reported no increase in risk of congenital malformations associated with the use of bupropion during pregnancy compared with other antidepressants as a group in women with depression during pregnancy. 153 Indirect evidence from a larger (N=7005), medium risk of bias study, also reported no statistically significant increase in risk with bupropion compared with other antidepressants reported an adjusted OR of 0.95 (95% CI, 0.62 to 1.45), 40 Depression status of women in either group was not known in this study.…”
Section: Class Compared With Class: Selective Serotonin Reuptake Inhimentioning
confidence: 64%
“…While there are a few other studies that report the risk of malformations after exposure during the conception period for individual or grouped SSRIs, SNRIs, and individual drugs, 40,49,79,152 none controlled for more than two of the key confounders, and suffered from inferior methods for ascertainment of exposure or outcomes.…”
Section: Key Question 2b In Babies Born To Women Who Become Pregnantmentioning
confidence: 99%
See 1 more Smart Citation
“…birthcertificate data) in the USA has previously been demonstrated to underrepresent outcomes of highrisk pregnancies, potentially introducing selection bias [Bronstein et al 2009]. An additional limitation of using claims databases from healthcare plans such as Medicaid, which is a healthcare plan for low-income persons, is that cohort members are not representative of those with private health insurance, limiting the generalizability of study findings [Cole et al 2007b]. Similarly, claims-based databases from private health insurers suffer from the limitation that analyses are restricted to those who maintain coverage with the health insurer during the defined study period, which could change as a result of changes in income, employment, and/or residence.…”
Section: Data Linkagementioning
confidence: 99%
“…25 Another study suggests that bupropion may be safe to use in pregnancy with no increased risk of teratogenic effects when used during the first trimester compared with other antidepressants or when used outside of the first trimester. 26 More research is necessary in order to make recommendations for the use of bupropion during pregnancy.…”
Section: Smoking Cessation Treatmentsmentioning
confidence: 99%